Cancer Chemoprevention and Piperine: Molecular Mechanisms and Therapeutic Opportunities - Rather, Rafiq A.; Bhagat, Madhulika (Frontiers in Cell and Developmental Biology, 2018)
Cancer is a genetic disease characterized by unregulated growth and dissemination of malignantly transformed neoplastic cells. The process of cancer development goes through several stages of biochemical and genetic alterations in a target cell. Several dietary alkaloids have been found to inhibit the molecular events and signaling pathways associated with various stages of cancer development and therefore are useful in cancer chemoprevention. Cancer chemoprevention has long been recognized as an important prophylactic strategy to reduce the burden of cancer on health care system. Cancer chemoprevention assumes the use of one or more pharmacologically active agents to block, suppress, prevent or reverse the development of invasive cancer. Piperine is an active alkaloid with an excellent spectrum of therapeutic activities such as anti-oxidant, anti-inflammatory, immunomodulatory, anti-asthmatic, anti-convulsant, anti-mutagenic, antimycobacterial, anti-amoebic and anti-cancer activities. In this article, we made an attempt to sum up the current knowledge on piperine that supports the chemopreventive potential of this dietary phytochemical. Many mechanisms have been purported to understand the chemopreventive action of piperine. Piperine has been reported to inhibit the proliferation and survival of many types of cancer cells through its influence on activation of apoptotic signaling and inhibition of cell cycle progression. Piperine is known to affect cancer cells in variety of other ways such as influencing the redox homeostasis, inhibiting cancer stem cell (CSC) self-renewal and modulation of ER stress and autophagy. Piperine can modify activity of many enzymes and transcription factors to inhibit invasion, metastasis and angiogenesis. Piperine is a potent inhibitor of p-glycoprotein (P-gp) and has a significant effect on the drug metabolizing enzyme (DME) system. Because of its inhibitory influence on p-glycoprotein activity, piperine can reverse multidrug resistance (MDR) in cancer cells and acts as bioavailability enhancer for many chemotherapeutic agents. In this article, we emphasize the potential of piperine as a promising cancer chemopreventive agent and the knowledge we collected in this review can be applied in the strategic design of future researches particularly human intervention trials with piperine.